EFFECT OF MALAY LANGUAGE PORTAL-BASED ASSESSMENT - Adenan Ayob; Lajiman Janoory, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
In this era of information and communication technology, one great mission shows that portal, digital and virtual element contributes to the development of assessment orientation structure. From that mission, researcher was trying to carry out related research. Thus, this research was conducted to review student’s achievement in Malay Language subject before and after exposed to portal-based assessment. Quasi-experimental method was used to review the mean difference before and after the students was exposed to the portal. The sample is 30 standard five primary students in the Federal Territory, Kuala Lumpur, Malaysia. The sample is an intact group that was determined by the school. The descriptive data are mean and standard deviation, while the inferential data is Paired Samples T Test. The results showed that there was significant difference between pre-test and post-test. As a conclusion, the Ministry of Education, Malaysia has to create a comprehensive portal-based assessment in the classroom in all states in Malaysia. It aims to activate the information technology implementation in the classroom. In terms of implication, this study can generate innovation in digital-based assessment in the classroom too.